Incisional Hernia in Renal Transplant Recipients: A Systematic Review. Issue 6 (June 2018) - Simson, Nick; Samuel, Parker; Stonier, Thomas; Halligan, Stephen; Windsor, Alastair
Incisional hernia follows midline laparotomy in 8 to 20 per cent of cases, but the rate following lateral incision is not well documented. This systematic review summarizes incisional hernia rate after open renal transplant. We searched EMBASE, MEDLINE, and the Cochrane Library databases from January 2000 to November 2016 inclusive. The outcomes included in our analysis were the posttransplant incisional hernia rate, significant patient risk factors for incisional hernia, the definition of incisional hernia used, the method used to detect incisional hernia, and the incision used for transplantation. Eight retrospective case series were identified, three describing renal transplant recipients and five describing incisional hernia repairs postrenal transplant. All reported the incisional hernia rate postrenal transplant at the host institution. The hernia rate ranged from 1.1 to 7.0 per cent, with a mean of 3.2 per cent. Factors associated with incisional hernia were body mass index >30, age >50, cadaveric graft, and reoperation through the same incision. Despite the significant comorbidity of renal transplant recipients, the incisional hernia rate postrenal transplant is significantly lower than that of post-midline laparotomy. The reasons for this are discussed. This demonstrates the importance of operative technique, local tissue quality and biomechanical factors in the formation of incisional hernia.